Peptides derived from Mycobacterium tuberculosis Rv2301 protein are involved in invasion to human epithelial cells and macrophages (2012)
The specific function of putative cut2 protein (or CFP25), encoded by the Rv2301 gene from Mycobacterium tuberculosis H37Rv, has not been identified yet. The aim of this study was to assess some of CFP25 characteristics and its possible biological role in Mycobacterium tuberculosis H37Rv invasion process to target cells. Molecular assays indicated that the gene encoding Rv2301 is present and transcribed in M. tuberculosis complex strains. The presence of Rv2301 protein over the bacilli surface was confirmed by Western blot and immunoelectron microscopy analyses, using goats sera inoculated with synthetic peptides derived from Rv2301 protein. Receptor-ligand binding assays with carcinomic human alveolar basal epithelial cells (A549) and macrophages derived from human histolytic lymphoma monocytes (U937) allowed us to identify five high activity binding peptides (HABPs) in both cell lines, and two additional HABPs only in A549 cells. U937 HABPs binding interactions were characterized by saturation assays, finding dissociation constants (K d) within the nanomolar range and positive cooperativity (n H and gt; 1). Inhibition assays were performed to assess the possible biological role of Rv2301 identified HABPs, finding that some of them were able to inhibit invasion at a 5 ?M concentration, compared with the cytochalasin control. On the other hand, HABPs, and especially HABP 36507 located at the N-terminus of the protein, facilitated the internalization of fluorescent latex beads into A549 cells. These findings are of vital importance for the rational selection of Rv2301 HABPs, to be included as components of an antituberculosis vaccine. © 2011 Springer-Verlag.